A composite lithium iron manganese phosphate positive electrode material and preparation method thereof

By forming a composite cladding layer of TiO2/g-C3N4 heterojunction and carbon on the surface of lithium manganese iron phosphate material, the problem of manganese dissolution and deposition of the material during charge and discharge is solved, and the conductivity and electrochemistry of the material are significantly improved. performance.

CN119038513BActive Publication Date: 2025-02-11SICHUAN FULIN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411539768.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Lithium manganese ferrophosphate material has problems of manganese dissolution and deposition during charging and discharging, resulting in material structure deterioration and electrochemical performance deterioration, especially during high-temperature cycles and storage processes.

Method used

The lithium manganese iron phosphate core is obtained by mixing the lithium source, iron source, manganese source, phosphorus source and the first carbon source, and reacting with the titanium-containing precursor and the nitrogen-rich precursor to form the TiO2/g-C3N4 heterogeneity A composite cladding of junction and carbon improves the structural stability and electrochemical properties of the material.

Benefits of technology

It effectively improves the manganese dissolution phenomenon in composite materials, avoids contact with the matrix material and the electrolyte and the occurrence of side reactions, improves the conductivity and electrochemical properties of the material, and enhances the application value of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119038513B_ABST
    Figure CN119038513B_ABST
Patent Text Reader

Abstract

A composite lithium iron manganese phosphate positive electrode material and a preparation method thereof, relating to the field of material technology, wherein the preparation method comprises mixing a lithium source, an iron source, a manganese source, a phosphorus source and a first carbon source and sintering the mixture to obtain a lithium iron manganese phosphate core; and then reacting and sintering the mixture with a titanium-containing precursor and a nitrogen-rich precursor respectively to obtain a composite lithium iron manganese phosphate positive electrode material. The preparation method is simple to operate and has low requirements on equipment, and realizes in-situ coating of a nanoscale TiO2 / g‑C3N4 heterojunction and a carbon material on the surface of a lithium iron manganese phosphate material, effectively improving the occurrence of manganese dissolution in the composite material, avoiding contact between the matrix material and the electrolyte, and the occurrence of side reactions caused thereby. At the same time, the TiO2 / g‑C3N4 heterojunction and carbon can synergistically improve the electrical contact between the material particles, enhance the ion transfer efficiency and electronic conductivity of the material surface, thereby improving the electrical conductivity of the material, ensuring its performance when applied to batteries, and having great application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a composite lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] With the growth of energy demand and increasingly severe environmental problems, the research and development of positive electrode materials for lithium-ion batteries, as an important energy storage device, has received widespread attention. At present, lithium iron phosphate occupies an important position in the market due to its good cycle performance and safety. Lithium iron manganese phosphate is regarded as an upgraded version of lithium iron phosphate. The two have the same theoretical capacity but different discharge platforms. Compared with lithium iron phosphate, lithium iron manganese phosphate has a higher voltage platform and an energy density that can be about 20% higher than that of lithium iron phosphate. It is expected to break through the upper limit of the current battery energy density and is a promising new positive electrode material for the next generation.

[0003] However, lithium manganese iron phosphate materials have problems with manganese dissolution and deposition during the charging and discharging process, which leads to degradation of the material structure and deterioration of the electrochemical performance. These problems are more prominent, especially during high-temperature cycling and storage, and limit their development and application.

[0004] Surface coating is a very effective and feasible solution to this problem. A large number of studies have shown that the introduction of a composite coating layer on the surface of the positive electrode material can avoid direct contact between the positive electrode material and the electrolyte, reduce the probability of side reactions, and effectively improve the structural stability of the material, thereby significantly improving the electrochemical performance of the material. Therefore, it is crucial to improve the structural stability and electrochemical performance of the positive electrode material by rationally designing the synthesis scheme and effectively controlling the synthesis process to obtain an effective construction of a uniform, dense and stable coating layer. Summary of the invention

[0005] The purpose of the present invention is to provide a composite lithium iron manganese phosphate positive electrode material and a preparation method thereof, so as to solve the problems of poor conductivity, manganese precipitation and electrolyte corrosion of the existing lithium iron manganese phosphate material, so as to improve the circulation and storage performance of the lithium iron manganese phosphate material.

[0006] The embodiment of the present invention is achieved as follows:

[0007] A method for preparing a composite lithium iron manganese phosphate positive electrode material, comprising:

[0008] The lithium source, the iron source, the manganese source, the phosphorus source and the first carbon source are mixed and sintered to obtain a lithium iron manganese phosphate core;

[0009] The lithium iron manganese phosphate core is ground and mixed with a titanium-containing precursor to obtain a titanium-containing composite material;

[0010] The titanium-containing composite material is mixed with a nitrogen-rich precursor and a second carbon source and then subjected to secondary sintering to obtain a composite lithium manganese iron phosphate positive electrode material.

[0011] A composite lithium iron manganese phosphate positive electrode material, which is prepared by the above-mentioned preparation method of the composite lithium iron manganese phosphate positive electrode material, the composite lithium iron manganese phosphate positive electrode material comprises a lithium iron manganese phosphate core and a TiO2 arranged on the surface of the lithium iron manganese phosphate core. 2 / gC 3 N 4 Heterojunction and carbon composite coating.

[0012] The beneficial effects of the embodiments of the present invention are:

[0013] The embodiment of the present invention provides a composite lithium iron manganese phosphate positive electrode material and a preparation method thereof. The preparation method comprises mixing a lithium source, an iron source, a manganese source, a phosphorus source and a first carbon source and sintering the mixture to obtain a lithium iron manganese phosphate core; and then reacting and sintering the mixture with a titanium-containing precursor and a nitrogen-rich precursor to obtain a composite lithium iron manganese phosphate positive electrode material. The preparation method is simple to operate, has low requirements on equipment, and realizes the nanoscale TiO 2 / gC 3 N 4 The heterojunction and carbon material are in-situ coated on the surface of lithium manganese iron phosphate material, which effectively improves the manganese dissolution phenomenon in the composite material, avoids the contact between the matrix material and the electrolyte, and the side reactions caused by it. 2 / gC 3 N 4 Heterojunction and carbon can synergistically improve the electrical contact between material particles, enhance the ion transfer efficiency and electronic conductivity on the material surface, thereby improving the electrical conductivity of the material and ensuring its performance when used in batteries, which has great application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0015] Figure 1 This is the SEM spectrum of the composite lithium iron manganese phosphate positive electrode material provided in Example 1 of the present invention;

[0016] Figure 2 This is the SEM spectrum of the composite lithium iron manganese phosphate positive electrode material provided in Comparative Example 3 of the present invention;

[0017] Figure 3The 0.1C charge and discharge capacity test graph of button cells prepared from the positive electrode materials of Examples 1 to 4 and Comparative Examples 1 to 5 of the present invention;

[0018] Figure 4 This is a test chart of 1C charge and discharge capacity of button batteries prepared from the positive electrode materials of Examples 1 to 4 and Comparative Examples 1 to 5 of the present invention. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0020] The following is a detailed description of a composite lithium manganese iron phosphate positive electrode material and a preparation method and application thereof according to an embodiment of the present invention.

[0021] The embodiment of the present invention provides a method for preparing a composite lithium iron manganese phosphate positive electrode material, which comprises:

[0022] S1. The lithium source, the iron source, the manganese source, the phosphorus source and the first carbon source are mixed and sintered to obtain a lithium manganese iron phosphate core;

[0023] S2. The lithium iron manganese phosphate core is ground and mixed with a titanium-containing precursor to obtain a titanium-containing composite material;

[0024] S3. The titanium-containing composite material is mixed with a nitrogen-rich precursor and a second carbon source and then subjected to secondary sintering to obtain a composite manganese iron phosphate lithium positive electrode material.

[0025] The preparation method is simple to operate and has low requirements on equipment. 2 / gC 3 N 4 Heterojunction and carbon material are in-situ coated on the surface of lithium manganese iron phosphate material. TiO 2 and gC 3 N 4 They belong to semiconductor materials with different energy band structures. The two are combined to form a heterojunction semiconductor structure, which has an adjustable energy band structure, a large specific surface area, an excellent pore structure, a higher conductivity and better electrochemical activity, thus making up for the problem of insufficient conductivity and manganese precipitation of lithium manganese iron phosphate in practical applications. 2 / gC 3 N 4Heterojunction and carbon can synergistically improve the electrical contact between material particles, enhance the ion transfer efficiency and electronic conductivity on the material surface, thereby improving the electrical conductivity of the material and ensuring its performance when used in batteries, which has great application value.

[0026] Among them, the lithium source, iron source, manganese source, phosphorus source, first carbon source, second carbon source, titanium-containing precursor, and nitrogen-rich precursor are all commercially available materials, and are uniformly ground to an average particle size of less than 500 nm before use.

[0027] Furthermore, the iron source includes at least one of ferrous oxalate, ferric phosphate, ferric acetate, ferric nitrate and ferric oxide; the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate and lithium dihydrogen phosphate; the manganese source includes at least one of manganese oxalate, manganese tetraoxide, manganese sulfate, manganese acetate and manganese nitrate; the phosphorus source includes at least one of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate and lithium dihydrogen phosphate.

[0028] Preferably, the molar ratio of Li:P:(Fe+Mn) provided by the lithium source, iron source, manganese source, and phosphorus source is 0.99-1.05:0.98-1.01:0.98-1.01. The molar ratio of Mn:Fe provided by the manganese source and iron source is 5:5-8:2. The overall performance of the material is better within the above ratio range.

[0029] The first carbon source and / or the second carbon source include at least one of glucose, sucrose, polyvinyl pyrrolidone or polyethylene glycol; the carbon content in the lithium iron manganese phosphate core does not exceed 0.5wt%; the total carbon content in the composite lithium iron manganese phosphate positive electrode material is 1wt%~3wt%. Within the above ratio range, it is conducive to forming a uniform carbon coating layer, which can improve the conductivity of the material.

[0030] Furthermore, the titanium-containing precursor includes at least one of ethyl titanate, isopropyl titanate, n-butyl titanate, titanyl sulfate, titanium chloride and titanium sulfate. The nitrogen-rich precursor includes at least one of melamine, dicyandiamide, cyanamide, urea and thiourea. After sintering, the titanium-containing precursor and the nitrogen-rich precursor are TiO 2 / gC 3 N 4 The heterojunction exists in the carbon coating layer of the composite lithium manganese iron phosphate positive electrode material; it effectively improves the manganese dissolution phenomenon in the composite material and further improves the electrical conductivity of the material.

[0031] Optionally, the TiO in the composite lithium manganese iron phosphate positive electrode material 2 / gC 3 N 4 The content of heterojunction is 0.2wt%~1wt%; TiO 2 / gC 3 N 4TiO in heterojunction 2 and gC 3 N 4 The mass ratio of is 1:0.2~0.8. Within the above range, the electrochemical performance of the composite manganese iron phosphate lithium positive electrode material is better improved.

[0032] The reaction temperature of the lithium manganese iron phosphate core and the titanium-containing precursor is 150-200°C, and the reaction time is 5-24 h. The heating rate during the reaction is controlled at 8-15°C / min. Under the above reaction conditions, it is more conducive to the conversion of the titanium-containing precursor into TiO 2 After the reaction is completed, spray drying can be used to remove the solvent, and then a secondary sintering operation can be performed. The temperature of sintering and secondary sintering is 500~800℃, and the duration is 5~12 hours. Both sintering and secondary sintering are carried out in an inert atmosphere, which is conducive to the formation of materials.

[0033] Further, the lithium iron manganese phosphate core is ground to a particle size D50 of 200-1200nm, and then mixed with a titanium-containing precursor for reaction. Preferably, the lithium iron manganese phosphate core is divided into core material A and core material B, and they are ground separately until the particle size D50 of core material A is 200-500nm, and the particle size D50 of core material B is 500-1200nm. The mass ratio of core material A to core material B is 5:5-9:1. Within the above-mentioned ratio range, the proportion of large and small particles in the positive electrode material of the present invention can be effectively controlled and maintained, thereby obtaining a better positive electrode material particle size distribution width, a better grading effect and a higher compaction density.

[0034] The present invention also provides a composite lithium iron manganese phosphate positive electrode material, which is prepared by the above-mentioned composite lithium iron manganese phosphate positive electrode material preparation method, and the composite lithium iron manganese phosphate positive electrode material includes a lithium iron manganese phosphate core and a TiO2 disposed on the surface of the lithium iron manganese phosphate core. 2 / gC 3 N 4 Heterojunction and carbon composite coating. The composite lithium manganese iron phosphate positive electrode material has an adjustable band structure, a large specific surface area, an excellent pore structure, a higher conductivity and better electrochemical activity, thus making up for the problems of insufficient conductivity and manganese precipitation of lithium manganese iron phosphate in practical applications.

[0035] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0036] Example 1

[0037] This embodiment provides a composite lithium manganese iron phosphate positive electrode material, and the preparation method thereof is as follows:

[0038] S1. Lithium carbonate, ferrous oxalate, manganese oxalate, lithium dihydrogen phosphate and polyethylene glycol (Mn:Fe:P:Li=0.582:0.388:1:1.04) were mixed and dispersed in an appropriate amount of methanol to form a uniform mixed slurry; then, the average particle size of the sample was reduced to below 500nm by wet sand milling and spray dried. Then, a sintering was performed in a nitrogen atmosphere, the sintering temperature was set to 550℃, and the constant temperature time was 5 hours, so as to obtain a lithium manganese iron phosphate core; the carbon content in the lithium manganese iron phosphate core was 0.35wt%.

[0039] S2. The lithium manganese iron phosphate core material is graded and ground to obtain core material A and core material B with different particle sizes, the mass ratio of core material A to core material B is 7:3; the particle size D50 of core material A is 0.3 μm, and the particle size D50 of core material B is 1.0 μm.

[0040] S3. Dissolve isopropyl titanate in methanol, add core material A and core material B to disperse into the above system, then transfer it to a polytetrafluoroethylene-lined autoclave, raise the temperature to 180°C at 10°C / min, keep warm for 4 hours, and cool naturally to room temperature.

[0041] S4. Add urea and sucrose to the above solvent thermal reaction system, stir evenly, spray dry and perform secondary sintering in an inert atmosphere. The sintering temperature is set to 700°C and the constant temperature time is 6 hours. Finally, a composite manganese iron phosphate lithium positive electrode material is obtained. The total carbon content of the composite manganese iron phosphate lithium positive electrode material is 1.8wt%. TiO 2 / gC 3 N 4 The heterojunction content is 0.5wt%; TiO 2 / gC 3 N 4 TiO in heterojunction 2 and gC 3 N 4 The mass ratio is 1:0.2.

[0042] The SEM spectrum of the composite lithium manganese iron phosphate positive electrode material prepared in this example is as follows Figure 1 As shown, the material has uniform particle size distribution, high sphericity and better compaction density.

[0043] Example 2

[0044] This embodiment provides a composite lithium manganese iron phosphate positive electrode material, and the preparation method thereof is as follows:

[0045] S1. Lithium hydroxide, iron phosphate, manganese tetraoxide, ammonium dihydrogen phosphate and polyvinyl pyrrolidone (Mn:Fe:P:Li=0.485:0.485:1:1.04) were mixed and dispersed in an appropriate amount of methanol to form a uniform mixed slurry; then, the average particle size of the sample was reduced to below 500 nm by wet sand milling and spray dried. Then, a sintering was performed in a nitrogen atmosphere, the sintering temperature was set to 550°C, and the constant temperature time was 5 hours, thereby obtaining a manganese iron phosphate lithium core; the carbon content in the manganese iron phosphate lithium core was 0.5wt%.

[0046] S2. The lithium iron manganese phosphate core material is graded and ground to obtain core material A and core material B with different particle sizes, the mass ratio of core material A to core material B is 5:5; the particle size D50 of core material A is 0.2 μm, and the particle size D50 of core material B is 0.8 μm.

[0047] S3. Dissolve titanyl sulfate in methanol, add core material A and core material B to disperse into the above system, then transfer it to a polytetrafluoroethylene-lined autoclave, raise the temperature to 180°C at 10°C / min, keep warm for 4 hours, and cool naturally to room temperature.

[0048] S4. Add melamine and glucose to the above solvent thermal reaction system, stir evenly, spray dry and perform secondary sintering in an inert atmosphere. The sintering temperature is set to 700°C and the constant temperature time is 8 hours. Finally, a composite manganese iron phosphate lithium positive electrode material is obtained. The total carbon content of the composite manganese iron phosphate lithium positive electrode material is 2wt%. TiO 2 / gC 3 N 4 The heterojunction content is 0.8wt%; TiO 2 / gC 3 N 4 TiO in heterojunction 2 and gC 3 N 4 The mass ratio is 1:0.6.

[0049] Example 3

[0050] This embodiment provides a composite lithium manganese iron phosphate positive electrode material, and the preparation method thereof is as follows:

[0051] S1. Lithium acetate, ferric acetate, manganese acetate, phosphoric acid and sucrose (Mn:Fe:P:Li=0.672:0.288:1:1.03) were mixed and dispersed in an appropriate amount of methanol to form a uniform mixed slurry; then, the average particle size of the sample was reduced to below 500nm by wet sand milling and spray dried. Then, a sintering was performed in a nitrogen atmosphere, the sintering temperature was set to 550℃, and the constant temperature time was 5 hours, thereby obtaining a lithium manganese iron phosphate core; the carbon content in the lithium manganese iron phosphate core was 0.3wt%.

[0052] S2. The lithium iron manganese phosphate core material is graded and ground to obtain core material A and core material B with different particle sizes, the mass ratio of core material A to core material B is 8:2; the particle size D50 of core material A is 0.4 μm, and the particle size D50 of core material B is 1.2 μm.

[0053] S3. Dissolve titanium chloride in methanol, add core material A and core material B to disperse in the above system, then transfer it to a polytetrafluoroethylene-lined autoclave, raise the temperature to 200°C at 12°C / min, keep warm for 8 hours, and cool naturally to room temperature.

[0054] S4. Add cyanamide and sucrose to the above solvent thermal reaction system, stir evenly, spray dry and perform secondary sintering in an inert atmosphere. The sintering temperature is set to 600°C and the constant temperature time is 10 hours. Finally, a composite manganese iron phosphate lithium positive electrode material is obtained. The total carbon content of the composite manganese iron phosphate lithium positive electrode material is 2wt%. TiO 2 / gC 3 N 4 The content of heterojunction is 1.0wt%; TiO 2 / gC 3 N 4 TiO in heterojunction 2 and gC 3 N 4 The mass ratio is 1:0.5.

[0055] The SEM spectrum of the composite lithium manganese iron phosphate positive electrode material prepared in this example is as follows Figure 2 As shown, the material has uniform particle size distribution, high sphericity and better compaction density.

[0056] Example 4

[0057] This embodiment provides a composite lithium manganese iron phosphate positive electrode material, and the preparation method thereof is as follows:

[0058] S1. Lithium hydroxide, ferric oxide, manganese nitrate, phosphoric acid and glucose (Mn:Fe:P:Li=0.582:0.388:1:1.035) were mixed and dispersed in an appropriate amount of methanol to form a uniform mixed slurry; then, the average particle size of the sample was reduced to below 500nm by wet sand milling and spray dried. Then, a sintering was performed in a nitrogen atmosphere, the sintering temperature was set to 650°C, and the constant temperature time was 7 hours, thereby obtaining a lithium manganese iron phosphate core; the carbon content in the lithium manganese iron phosphate core was 0.4wt%.

[0059] S2. Grind the lithium manganese iron phosphate core material until the particle size D50 is 0.6 μm.

[0060] S3. Dissolve isopropyl titanate in methanol, add lithium iron manganese phosphate core material and disperse it into the above system, then transfer it to a polytetrafluoroethylene-lined autoclave, raise the temperature to 180°C at 10°C / min, keep it for 4 hours, and cool it naturally to room temperature.

[0061] S4. Add urea and sucrose to the above solvent thermal reaction system, stir evenly, spray dry and perform secondary sintering in an inert atmosphere. The sintering temperature is set to 550°C and the constant temperature time is 6 hours. Finally, a composite manganese iron phosphate lithium positive electrode material is obtained. The total carbon content of the composite manganese iron phosphate lithium positive electrode material is 2.5wt%. TiO 2 / gC 3 N 4 The heterojunction content is 0.5wt%; TiO 2 / gC 3 N 4 TiO in heterojunction 2 and gC 3 N 4 The mass ratio is 1:0.2.

[0062] Comparative Example 1

[0063] This comparative example provides a composite lithium iron manganese phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that step S3 is eliminated, and core material A and core material B are directly dispersed in methanol, and then step S4 is performed to mix with urea and sucrose.

[0064] Comparative Example 2

[0065] This comparative example provides a composite lithium iron manganese phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that urea is not added in step S4.

[0066] Comparative Example 3

[0067] This comparative example provides a composite lithium iron manganese phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that step S3 is eliminated, and core material A and core material B are directly dispersed in methanol, and then step S4 is performed; and urea is not added in step S4.

[0068] Comparative Example 4

[0069] This comparative example provides a composite lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the amount of titanium-containing precursor and nitrogen-rich precursor is increased, so that TiO 2 / gC 3 N 4 The heterojunction content is 5wt%, TiO 2 / gC 3 N 4 TiO in heterojunction 2 and gC 3 N 4 The mass ratio remains unchanged.

[0070] Comparative Example 5

[0071] This comparative example provides a composite lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the amount of nitrogen-rich precursor is increased so that TiO 2 / gC 3 N 4 TiO in heterojunction 2 and gC 3 N 4 The mass ratio is 1:2.

[0072] Test Example 1

[0073] The composite lithium iron manganese phosphate positive electrode materials provided in Examples 1 to 3 and Comparative Examples 1 to 5 were used as battery positive electrode materials for assembly and testing. The gram capacity at 0.1C and 1C rates was tested respectively. The charge and discharge curves are shown in FIG. Figure 3 and Figure 4 The test results are shown in Table 1.

[0074] Table 1. Test results of composite manganese iron phosphate lithium cathode material

[0075]

[0076] It can be seen from Table 1 that after the manganese-iron ratio and the heterojunction coating amount are precisely controlled in Examples 1 to 4 of the present invention, the resulting products exhibit excellent performance characteristics. Especially in terms of charge and discharge performance, these embodiments all show significant advantages. Specifically, taking the preparation process of Example 1 as an example, we successfully achieved a compaction density of up to 2.423g / cm³, which is at the leading level among similar products. At the same time, the manganese dissolution amount under this embodiment is as low as 5.20ppm, showing extremely high material stability. In addition, the powder resistivity also reached an excellent 12.166 Ω·cm, ensuring the transmission of electrons in the material. It is worth mentioning that at a rate of 0.1C, the first discharge capacity of this embodiment is as high as 153.045mAh / g, which fully demonstrates its potential in practical applications.

[0077] In contrast, in Comparative Examples 1 and 2, no titanium-containing precursor and nitrogen-rich precursor were added, and only one material was doped in the obtained carbon coating layer. It can be seen that the manganese dissolution amount increased significantly, directly increasing to 10.85~15.49ppm compared with the dissolution amount of Example 2.23~5.20ppm. At the same time, the increase in powder resistivity was also quite significant, increasing to 24.432~36.775Ω·cm, and the first discharge gram capacity also decreased to a certain extent.

[0078] Furthermore, in Comparative Example 3, in which no titanium-containing precursor and nitrogen-rich precursor were added at the same time, the manganese dissolution amount and powder resistivity increased significantly, reaching 46.84ppm and 62.022Ω·cm respectively, and the 0.1C discharge specific capacity also decreased to a certain extent, further highlighting the key role of heterojunction surface coating in improving product performance.

[0079] In Comparative Example 4, we added TiO 2 / gC 3 N 4 Although the coating amount of the heterojunction showed a better inhibitory effect on manganese dissolution, the 0.1C discharge specific capacity was significantly reduced, reaching only 136.544 mAh / g, indicating that excessive coating amount had a negative impact on the electrical performance of the product.

[0080] In Comparative Example 5, we adjusted the TiO 2 and gC 3 N 4 The mass ratio of , leads to a slight increase in manganese dissolution and powder resistivity, indicating that in the pursuit of optimal performance, we need to fine-tune the heterojunction coating amount to find the best balance.

[0081] In summary, the embodiment of the present invention provides a composite lithium iron manganese phosphate positive electrode material and a preparation method thereof. The preparation method comprises mixing a lithium source, an iron source, a manganese source, a phosphorus source and a first carbon source and sintering the mixture to obtain a lithium iron manganese phosphate core; and then reacting and sintering the mixture with a titanium-containing precursor and a nitrogen-rich precursor to obtain a composite lithium iron manganese phosphate positive electrode material. The preparation method is simple to operate, has low requirements on equipment, and realizes the nanoscale TiO 2 / gC 3 N 4 The heterojunction and carbon material are in-situ coated on the surface of lithium manganese iron phosphate material, which effectively improves the manganese dissolution phenomenon in the composite material, avoids the contact between the matrix material and the electrolyte, and the side reactions caused by it. 2 / gC 3 N 4 Heterojunction and carbon can synergistically improve the electrical contact between material particles, enhance the ion transfer efficiency and electronic conductivity on the material surface, thereby improving the electrical conductivity of the material and ensuring its performance when used in batteries, which has great application value.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite lithium manganese iron phosphate positive electrode material, characterized in that: include: The lithium source, the iron source, the manganese source, the phosphorus source and the first carbon source are mixed and sintered to obtain a lithium iron manganese phosphate core; Grinding the lithium iron manganese phosphate core and mixing it with a titanium-containing precursor to obtain a titanium-containing composite material; The titanium-containing composite material is mixed with a nitrogen-rich precursor and a second carbon source and then subjected to secondary sintering to obtain the composite lithium iron manganese phosphate positive electrode material; after sintering, the titanium-containing precursor and the nitrogen-rich precursor exist in the carbon coating layer of the composite lithium iron manganese phosphate positive electrode material in the form of a TiO2 / g-C3N4 heterojunction; the content of the TiO2 / g-C3N4 heterojunction in the composite lithium iron manganese phosphate positive electrode material is 0.2wt%~1wt%; the mass ratio of TiO2 and g-C3N4 in the TiO2 / g-C3N4 heterojunction is 1:0.2~0.

8.

2. The preparation method according to claim 1, characterized in that: The iron source includes at least one of ferrous oxalate, ferric phosphate, ferric acetate, ferric nitrate and ferric oxide; the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate and lithium dihydrogen phosphate; the manganese source includes at least one of manganese oxalate, manganese tetraoxide, manganese sulfate, manganese acetate and manganese nitrate; the phosphorus source includes at least one of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate and lithium dihydrogen phosphate.

3. The preparation method according to claim 1, characterized in that: The molar ratio of Mn:Fe provided by the manganese source and the iron source is 5:5-8:

2.

4. The preparation method according to claim 1, characterized in that: The first carbon source and / or the second carbon source include at least one of glucose, sucrose, polyvinyl pyrrolidone or polyethylene glycol; the carbon content in the lithium iron manganese phosphate core does not exceed 0.5wt%; the total carbon content in the composite lithium iron manganese phosphate positive electrode material is 1wt%~3wt%.

5. The preparation method according to claim 1, characterized in that: The titanium-containing precursor includes at least one of ethyl titanate, isopropyl titanate, n-butyl titanate, titanyl sulfate, titanium chloride and titanium sulfate; the nitrogen-rich precursor includes at least one of melamine, dicyandiamide, cyanamide, urea and thiourea.

6. The preparation method according to claim 1, characterized in that: The reaction temperature of the lithium manganese iron phosphate core and the titanium-containing precursor is 150-200° C., and the reaction time is 5-24 h.

7. The preparation method according to claim 1, characterized in that: The temperatures for sintering and secondary sintering are both 500~800℃, and the durations are both 5~12h.

8. The preparation method according to claim 1, characterized in that: The lithium manganese iron phosphate core is ground to a particle size D50 of 200-1200 nm, and then mixed with the titanium-containing precursor for reaction.

9. A composite lithium manganese iron phosphate positive electrode material, characterized in that: The composite lithium iron manganese phosphate positive electrode material is prepared by the preparation method of the composite lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 8, wherein the composite lithium iron manganese phosphate positive electrode material comprises the lithium iron manganese phosphate core and a TiO2 / g-C3N4 heterojunction and a carbon composite coating layer arranged on the surface of the lithium iron manganese phosphate core.

Citation Information

Patent Citations

  • High-performance lithium manganese iron phosphate composite material as well as preparation method and application thereof

    CN117936736A

  • Titanium-modified lithium iron manganese phosphate-based material as well as preparation method and application thereof

    CN117976849A